The Effectiveness Of Film Therapy In Developing Empathy For University Students In Faculty Of Science And Technology Uin Raden Fatah Palembang - Zaki, Nurul Melani; Amriyadi, Syalsabila Muhyi; Klisnawati, Jelis (CV. Era Digital Nusantara, 2024)
The study aims to further research on how film therapy can improve our empathy for university students at raden fatah palembang university of science and technology. The study used experimental research with a design of one group pre-testing post-test randomized the design. Subjects on the study are the 15 active students of the 2021 class science and technology faculty taken from the entire student council of science and 2021 class technology by sampling methods. Studies suggest that film therapy is effective in improving student empathy levels based on the average score of students' empathy on posttests (53.47) is significantly higher than before they received film therapy at pretest (48.00). This suggests a positive effect of film therapy on a student's empathy so it can be concluded that film therapy is an effective tool to enhance a student's empathy.